PENDAMPINGAN PROJECT REAL KEWIRAUSAHAAN SINGKONG CIMANGGU DI SMK NEGERI 1 BORONG - Noywuli, Nicolaus; Kaleka, Marten Umbu; Nono, Elfridus Andi Loke; Hamakonda, Umbu A; Lea, Victoria Coo (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Vocational High School (SMK) is a vocational education institution that focuses on mastering the knowledge, skills, and attitudes needed in the industrial and entrepreneurial worlds. This community service activity is carried out for one year per the cooperation contract, including planning and making guidelines for two months, cultivating mentoring activities for nine months, and evaluating activity implementation for one month. The cassava entrepreneurship project cultivation mentoring activities on the SMKN 1 Borong land went well, accompanied by the involvement of the team and teachers and the government represented by the SMA/K supervisor coordinator of East Manggarai Regency. The implementation of the entrepreneurship project at SMKN 1 Borong has followed the guidelines that the team has made from the Flores Bajawa Agricultural College.